(untitled) (Proceedings of International Educators Conference, 2023)
In the Surkhandarya region of the Republic of Uzbekistan, 26 family polyclinics and 15 family medical centers have been launched in the past 2 years, and 15 this year, in order to make the primary medical service closer to the population.